Olanzapine induced hyponatremia and rhabdomyolysis - N'joumi Younes; Haimeur Yassine; El Harfaoui Yassine; Benhlima Abdelkader; Elhamzaoui Hamza; Alilou Mustapha (Clinical Case Reports, 2023)
Abstract Rapid‐onset hyponatremia and rhabdomyolysis are rare, but potential, complications of olanzapine treatment. Hyponatremia, secondary to atypical antipsychotic use, has been reported in many case reports and is thought to be associated with an inappropriate antidiuretic hormone secretion syndrome. We report a case of sudden‐onset hyponatremia associated with a severe rhabdomyolysis resulting in a coma‐necessitating intensive care unit admission. His evolution was favorable after correction of all his metabolic disorders and olanzapine suspension.